Generalized Chebyshev-like Approximation for Low-pass Filter - Swady, Hisham L. (Iraqi Journal for Electrical and Electronic Engineering, 2011)
Analog filters constitute indispensible component of analog circuits and still playing an important part in interface with analog real world. realizing filters with odd order is preferred because of its time response . Therefore, this paper is conducted to introduce a new generalized Chebyshev – like approximation for analog filters. The analyses presented to realize the filters with odd order. This proposed novel approach offer good results in terms of flat delay and time domain response. Also, the achieved results are validated by comparison to normal Chebyshev filter via investigation several examples .